VIROLOGICAL RESPONSES OF VELPATASVIR/SOFOSBUVIR IN PATIENTS WITH HCV GENOTYPE 3 - Muhammad Sarfraz; Arshad Rabbani; Muhammad Shahzad Manzoor; Benish Adil (Journal of University Medical & Dental College, 2020)
BACKGROUND & OBJECTIVE: The role of Velpatasvir/Sofosbuvir in the treatment of hepatitis C virus type 3 infection is evaluated in terms of virologic responses. i.e Rapid Virological Response (RVR) End of treatment response (ETR) and Sustained virological response (SVR 12).METHODOLOGY: This was a descriptive case study conducted in Liver OPD of Benazir Bhutto Hospital during 01 November 2018 to 30 April 2019 , in which 100 patients of HCV were enrolled, all of them had HCV genotype 3 infection. Every patient was treated with combination of Velpatasvir/Sofosbuvir 100mg/400 mg Once Daily as part of treatment regimen of HCV infection for 12 weeks. Pre-treatment HCV RNA QUANTITATIVE PCR was done, which was repeated on 4, 12 weeks of treatment and then 12 weeks post treatment.RESULTS: Among 100 patients, 51 (51%) were male and 49 (49%) were females. Mean age of patients was 43.2 ± 10.4 years (mean ± SD). Mean BMI of enrolled patients was 21.34 ± 2.40 kg/m2. 33% patients were cirrhotic while 67% were non cirrhotic. 53% patients were treatment experienced while 47% were treatment naïve. Rapid Virological Response (RVR) was achieved in 92%, End of treatment response (ETR) was achieved in 96%, while Sustained Virological response (SVR12) was achieved in 99% patients. The results were stratiﬁed according to age, gender and BMI. There was no eﬀect of these parameters on the ﬁnal results.CONCLUSION: Virological response (RVR, ETR, SVR12) of Velpatsvir /Sofosbuvir and Ribavirin is encouraging.